IMPLIKASI YURIDIS PERATURAN KEJAKSAAN REPUBLIK INDONESIA NOMOR 15 TAHUN 2020 TENTANG PENGHENTIAN PENUNTUTAN BERDASARKAN KEADILAN RESTORATIF TERHADAP TERSANGKA TINDAK PIDANA - Rosadi, Otong; Satria, Aswad (UNES Law Review, 2022)
The Republic of Indonesia Prosecutor's Office Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice is the legal basis used by the Republic of Indonesia Prosecutor's Office in resolving minor crimes through restorative. Based on this regulation, the Pariaman District Prosecutor's Office for the last 2 (two) years from 2020 to June 2022 succeeded in resolving criminal acts that occurred with the concept of Restorative Justice as part of law enforcement. two) cases, 2 (two) cases of torture. The approach used in this study is a normative juridical approach which is supported by an empirical juridical approach. The data used are secondary data as the main data and primary data as supporting data, which were collected through library research and field studies with interview techniques. All data were then compiled and analyzed qualitatively, and presented in a qualitative descriptive form. Results Based on the research it can be explained that: First, the Juridical Implications of the Republic of Indonesia Prosecutor's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice Against Criminal Suspects, the Pariaman District Prosecutor's Office succeeded in committing 4 (four) criminal acts throughout 2020 until June 2022 with the Restorative Justice Method. However, only 2 (two) criminal acts ended peacefully and did not proceed to the District Court. Second, the obstacles faced by the Prosecutor's Office in implementing the Regulation of the Prosecutor's Office of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice against suspects of criminal acts consist of legal and non-legal obstacles. The legal obstacle is that the position of the prosecutor's regulation itself is not strong enough because the process of delaying the regulation is only regulated by a Ministerial-level regulation. Non-legal constraints have 2 (two) parts, namely Internal and External Constraints